PELATIHAN PEMBUATAN PUPUK ORGANIK PADAT DAN PUPUK ORGANIK CAIR PADA KELOMPOK TANI MELATI DESA SUNSEA KECAMATAN NAIBENU KABUPATEN TIMOR TENGAH UTARA - Maria Magdalena Endah Mulat Satmalawati; Kristina Mahus; Yanuario Seran; Jesika K. Jesika K; Usatnesi Usatnesi; Bernadina Metboki (Universitas Mataram, 2026)
This training activity is a community service activity and one part of the Practical Work Lecture carried out by students of the Agrotechnology Study Program, Faculty of Agriculture, Science and Health, University of Timor. This training aims to increase the understanding and skills of the Melati Farmer Group, Desa Sunsea, Kecamatan Naibeneu, Kabupaten Timor Tengah Utara (TTU) in utilizing the surrounding potential for making liquid and solid organic fertilizer. Organic fertilizer has many benefits, including increasing soil fertility, reducing dependence on chemical fertilizers, and supporting agricultural sustainability. This training activity involved 23 participants consisting of 20 members of the Melati Farmers Group and 3 students and was divided into two stages of activities. The first stage focuses on the practice of making solid organic fertilizer from forage and livestock manure, and continues with the second stage, namely making liquid organic fertilizer using the same raw materials. The results of this activity show an increase in the knowledge and skills of the community, especially the Sunsea Village Melati Farmers Group, and this is realized by applying organic fertilizer to the land of various cultivated plants.